Meat Intake and Insulin Resistance in Women without Type 2 Diabetes - Larry A. Tucker; James D. LeCheminant; Bruce W. Bailey (Journal of Diabetes Research)
Purpose. To examine the relationship between meat intake and insulin resistance (IR) in 292 nondiabetic women. Methods. IR was evaluated using the homeostasis model assessment (HOMA). Diet was assessed via 7-day weighed food records. Servings of very lean meat (VLM) and regular meat (meat) were indexed using the ADA Exchange Lists Program. Physical activity was assessed using accelerometers and body fat was measured using the Bod Pod. Results. Meat intake was directly related to HOMA (F = 7.4; P = 0.007). Women with moderate or high meat intakes had significantly higher HOMA levels than their counterparts. Adjusting for body fat weakened the relationship (F = 1.0; P = 0.3201). Odds ratio results showed that the low meat quartile had 67% lower odds of being IR (75th percentile) compared to their counterparts (OR = 0.33; 95% CI = 0.16–0.71). These findings changed little after adjusting for all covariates simultaneously (OR = 0.34; 95% CI = 0.14–0.83). Conversely, VLM intake was not related to HOMA, with or without the covariates. Conclusion. Moderate and high meat intakes are associated with increased insulin resistance in nondiabetic women. However, differences in body fat contribute significantly to the relationship. VLM is not predictive of IR. Prudence in the amount and type of meat consumed may be helpful in decreasing the likelihood of IR.